Advantages of Immunohistochemical Assessment of Inflammation of the Nasal Cavity and Paranasal Sinuses in Allergic Rhinitis - Ulmasov A.O. (Genius Journals, 2023)
The use of the latest achievements of rhinosurgery allows you to influence only the final result of the pathological process, without affecting the cause and pathogenesis of polyposis, therefore, does not exclude the recurrence of the disease. Therefore, the problem of treating polypous rhinosinusitis should be considered primarily from a therapeutic, and not from a surgical standpoint. A detailed study of the etiopathogenesis of this disease, the creation of a base for the development of new highly effective and safe medications will allow for long-term remission, and possibly a complete cure. Despite numerous studies in this area, there is still no single view on the ethnology and pathogenesis of nasal polyposis. There are a large number of theories, but none of them explains all the causes and mechanisms of the development of this disease. The key role of cytokine-regulated eosinophil migration is generally recognized [Gevaert Ph., 2006]. The release of mediators such as histamine, tryptase, prostaglandin D2, leukotrienes (B4 and C4) and kinins is considered significant during the degranulation of mast cells of the submucosal layer of the nasal mucosa
Keywords: Paranasal sinus; allergic rhinitis; morphology; assessment